Impression Cytology of Bulbar Conjunctiva in Refractive Patients - A. V. Doga; S. A. Borzenok; I. A. Mushkova; A. N. Karimova; M. R. Obraztsova; M. Kh. Khubetsova; D. S. Ostrovskiy (Oftalʹmologiâ, 2025)
Actuality. Maintaining a healthy eye surface is very important both for performing high-quality visual work and for maintaining a socially active lifestyle. A stable and functional tear film is necessary to protect and maintain the normal balance of the eye surface.Purpose: to determine the density of goblet cells of the bulbar conjunctiva in refractive profile patients at the pre- and postoperative stages, taking into account the condition of the ocular surface.Patients and methods. Within the framework of this work, 62 (62 eyes) refractive profile patients were examined, their average age was 26.5 ± 2.1 years. In addition to the standard refractive diagnosis, which determines the possibility of safe keratorefractive surgery, all patients underwent an assessment of the status ocular surface: Schirmer-1 test, Norn test, staining of the ocular surface with 0.1% fluorescein and 0.1% lissamine green, determination of tear film break up time and loss of meibomian gland secretion during upper meibography and the lower eyelid on the diagnostic module of the Mediworks slit lamp (China). The follow-up periods were before surgery, 1 week, 1, 3 and 6 months after surgery.Results. The results of this study showed an uneven distribution of goblet cell density in all study groups, followed by recovery the 6th month.Conclusion. Thus, the results of assessing condition of the ocular surface using standard ophthalmological research methods and using a modern diagnostic module for screening dry eye syndrome corresponded to the normal course of the recovery period after keratorefractive surgery against the background of prescribed targeted therapy in the fight against induced dry eye syndrome, while a study of the number of goblet cells showed the presence of changes, in groups with the initial presence of dry eye syndrome, this confirms high informative value and diagnostic significance of impression cytology.